Assessing Effectiveness of Multipurpose Voucher Scheme to Enhance Contraceptive Choices, Equity, and Child Immunization Coverage: Results of an Interventional Study from Pakistan - Ali M (Journal of Multidisciplinary Healthcare, 2020)
Moazzam Ali,1 Syed Khurram Azmat,2 Hasan Bin Hamza,3 Md Mizanur Rahman4 1Department of Sexual and Reproductive Health and Research, World Health Organization, Geneva, Switzerland; 2Department of Technical Services, Greenstar Social Marketing, Karachi, Pakistan; 3Health Policy, System Strengthening and Information Analysis Unit, Ministry of National Health Services, Regulations and Coordination, Islamabad, Pakistan; 4Department of Global Health Policy, School of International Health, The University of Tokyo, Tokyo, JapanCorrespondence: Moazzam AliDepartment of Sexual and Reproductive Health and Research, World Health Organization, Avenue Appia 20, Geneva 27 CH-1211, SwitzerlandTel +41 (22) 791 3442Email alimoa@who.intBackground: Pakistan has a high total fertility and unmet contraceptive need and is the fifth most populous country. This research aims to assess the effectiveness of a subsidized, multi-purpose voucher intervention to enhance the client–provider interaction for improved contraceptive counseling resulting in a potential increase in the modern methods uptake, continued use, and its impact on equity through better targeting, while increasing uptake of postnatal care and child immunization among women from the lowest two wealth quintiles in rural and urban communities of Punjab province, Pakistan.Methods: We used a quasi-experimental design with pre- and post-phases in intervention and control sites in Punjab province (August 2012–March 2015). To detect a 20% increase in modern contraceptive prevalence rate compared to baseline, 1276 women were enrolled in each arm. Difference-in-differences (DID) estimates are reported for key variables. Absolute and relative index of inequality including concentration curves and concentration index are used to describe the magnitude and extent of equity.Results: With no net increase in modern contraception use, the intervention area, however, reported a low modern method discontinuation rate. Vaccination rates for BCG increased significantly by 14%, and 5% each for DPT, HBV, and measles. Concentration index and slope index of inequalities for first-time use of modern contraceptives, knowledge of contraceptives, receiving ANC, and delivery at health facilities were negative, indicating that the use of these services was more concentrated among the disadvantaged in intervention areas than the wealthy counterparts.Conclusion: This Greenstar-led multiple voucher model did not significantly increase modern contraceptive use in the intervention study area but positively impacted equity. The integrated approach combining contraception with child immunization led to an increase in immunization coverage. It will be important for public policy decision-makers to assess the usefulness of this approach, as a long-term provision of free contraceptive services may lead to dependency in targeted communities.Keywords: vouchers, contraceptives, family planning, equity, immunization, Pakistan